Simulation of airflow at Vernadsky station for multi-site damage identification - Tsybulnyk, S.; Komenchuk, I.; Tymchenko, A. (Український антарктичний журнал, 2017)
Relevance of the study is that the consequences of premature destruction of the fuel tank or the wall of the building of the Ukrainian Antarctic Akademik Vernadsky station (Vernadsky station) may result in significant financial costs and human lives as a result of multi-site damage. Therefore, the main objective of the study is to identify the most probable places of snow accumulation and maximum wind pressure zones for identification and prevention of multi-site damage of buildings and engineering structures.